Experience History Interpreting America's Past - Davidson, James West; Brian DeLay; Christine Leigh Heyrman; Mark H. Lytle; Michael B. Stoff (New York : McGraw-Hill Higher Education, ©2011., 2010)
"Experience History emphasizes that history is not just a collection of proven facts, but is "created" from the detective work of historians examining evidence from the past. Providing the interactive environment that only an integrated solution can pro
Keywords: United States - History; World History